Visualisasi Agama di Ruang Publik: Komodifikasi, Reproduksi Simbol dan Maknanya - Rahman, Mujibur (Humanistika : Jurnal Keislaman, 2018)
AbstractÂ Religion is an omnipresent entity that is present everywhere and anytime. Religion as a system of values and norms became the reference of his people in worship, thinking and acting. The presence of religion in public space can then be understood from this character or trait. Religious presence is not always of value and doctrine or way of life, but is also present through material and visual forms, propagated through the media and all existing instruments. Religion, especially after the invention of the printing press and the internet technology revolution, became a new phenomenon that was represented in various forms. Religious commodities, religious commodities, and religious visualizations in todays technological era are a necara phenomenon. This paper wants to review the new phenomenon of religious visualization that now must be realized began to be an option to be displayed in the public space through what is referred to as visual merchandising. Visualization of religion here can not be separated from the context of religious commodification that has been reviewed by intellectuals and previous research, where religion is regarded as part of a market commodity that can be used as a tool to bring profit. Further religious visualization is not just a commodification, but a new style of religious adherents to affirm the existence of this religion. This paper finds that the visual of the religion that many appear in the public space, whether it is realized or not has become an interesting new phenomenon to be discussed.Â Keywords: Visualization of religion, commodification of religion, visual merchandising, public spaceÂ